(untitled) (Eurasian Medical Research Periodical, 2024)
We examined 500 young men of military age (average age 18.8±2.1) using television capillaroscopy of the nail beds of the upper extremities. of them – 280 people with neurocirculatory asthenia of the cardiac type and 170 young men with neurocirculatory asthenia of the hypertensive type. The control group consisted of 50 practically healthy young men. Conducted studies of the state and structure of the microcirculatory bed using telecapillaroscopy of the nail bed of the upper extremities in patients with neurocirculatory asthenia allowed us to come to the conclusion that there are no specific changes in microvessels and microdynamics in these patients